The Concept of BEAUTY in “The Picture of Dorian Gray” by O. Wilde - Bobomurodova Gulhayo Ismoil qizi (International Journal of Formal Education, 2024)
The article analyzes of cultural concepts functioning in the literary text leads to that: cultural concepts place a conceptually relevant role in the literary text, cultural concepts are regarded as content-thematic dominants of the text and embodiment of certain cultural.